Analisis Pengaruh Arah Lemparan Batuan Berdasarkan Initiation Point Terhadap Ground Vibration Pada Aktivitas Peledakan Di Pit Blok Osor Timur PT. Katika Selabumi Mining Kabupaten Kutai Kartanegara: Analisis Ground Vibration - Suhari, Josh Immanuel Stevano; Revia Oktaviani,; Albertus Juvensius Pontus, (ReTII, 2024)
Ground vibrations are waves that occur in the ground caused by an energy source. Ground vibrations due to blasting activity can affect buildings around the blasting area, including residential areas. Large peak particle velocity (PPV) can cause damage to people's homes. Data collection was carried out by dividing the data population into two, the direction of rock throwing based on the initiation point away from the measurement point and the direction of rock throwing based on the initiation point approaching the measurement point. During the research, values ​​were obtained PPV maximum is 3.03 mm/s with the initiation point close to the measurement point and there is a free face and walls at the blasting location, the PPV minimum of 0.4 mm/s with the initiation point away from the measurement point and there is a free face at the blasting location. Based on the results of calculating the predicted PPV value, an error percentage of 15.74% was obtained with the actual PPV value at the research location. From the results of the analysis and calculations, it was found that the direction of the rock throw with the initiation point closer to the measurement point had a greater value.